Surface Roughness Changes and Corrosion on Nickel Titanium Orthodontic Wires Compared to Stainless Steel Wires in Various Artificial Salivas - Kucukyildirim, Bedri Onur; Eker, Aysegul Akdogan (CARL HANSER VERLAG, 2012)
Nickel titanium shape memory alloy and stainless steel orthodontic wires were exposed to three different artificial saliva solutions which are modified Fusayama, modified Fusayama with 1g/1 NaF addition and modified Fusayama with 1.7 % H3PO4 addition. Under conditions similar to oral cavity temperature, corrosion behaviours were observed by using weight loss method and by macro surface photographic observations. Also, surface roughness of wires were investigated and compared. Consequently, it was determined that corrosion rates of all NiTi wires exposed to the modified Fusayama solutions with NaF addition are higher because of galvanic interaction of NiTi and hydrogen embrittlement of titanium. Also, surface roughness of NiTi wires were increased in modified Fusayama solution with NaF addition.
Keywords: FLUORIDE; NITI; RESISTANCE; Materials Science